2020
DOI: 10.1097/iae.0000000000002576
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Total and Inner Retinal Thicknesses in Type 1 Diabetes With No Retinopathy After 8 Years of Follow-Up

Abstract: Purpose: To evaluate changes in retinal layer thickness in patients with Type 1 diabetes with no diabetic retinopathy after 8 years of follow-up. Methods: Ninety Type 1 diabetes and 60 control eyes were studied. Changes in the retinal nerve fiber layer, ganglion cell layer, and inner nuclear layer thicknesses in all Early Treatment Diabetic Retinopathy Study areas were evaluated. Results: The mean ages were 42.93 ± 13.62 and 41.52 ± 13.05 years in the diabetic and control group, respectively. In 2009, total re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…The latest eight-year observations have revealed that the reduction in the thickness of the internal retinal layer takes place in T1DM patients along with the course of the disease but still before the DR manifestation. This confirms the hypothesis of retinal neurodegeneration [116].…”
Section: A Potential Link Between Retinal Neurodegeneration and Microsupporting
confidence: 91%
See 1 more Smart Citation
“…The latest eight-year observations have revealed that the reduction in the thickness of the internal retinal layer takes place in T1DM patients along with the course of the disease but still before the DR manifestation. This confirms the hypothesis of retinal neurodegeneration [116].…”
Section: A Potential Link Between Retinal Neurodegeneration and Microsupporting
confidence: 91%
“…The American Diabetes Association (ADA) recommends a reduction in HbA1C to <7%, maintenance of arterial blood pressure at <130/80 mm Hg and serum LDL <100 mg/dl (<70 mg/dl in patients with diagnosed cardiovascular disease). Such action will allow for a reduced risk of microvascular and cardiovascular complications also involving endothelial dysfunction [116]. In individuals who had increased their physical activity and changed eating habits a decrease was observed in the occurrence of diabetes and its vascular complications from 29% to 58% [126][127][128].…”
Section: Discussionmentioning
confidence: 99%
“…In humans with diabetes but no DR, OCT measurements in vivo have shown smaller total retinal thickness (Bronson-Castain et al, 2012;Chen et al, 2016), retinal nerve fiber layer (RNFL) (Lopes de Faria et al, 2002;Verma et al, 2012;Gundogan et al, 2016), ganglion cell layer (GCL) (Van Dijk et al, 2010), and inner retina (Karti et al, 2017). Other studies have not found retinal thinning (Park et al, 2011;Dhamdhere et al, 2012), suggesting that this is something that develops over the course of diabetes (Pinilla et al, 2020). In animal models, OCT measurements in mice found reduced thickness 4-8 weeks post diabetes development/induction (Hombrebueno et al, 2014;Sergeys et al, 2019).…”
Section: Changes In In Vivo Inner Retinal Activity Before the Developmentioning
confidence: 99%
“…Kim et al followed up type 2 diabetic patients for ≥4 years and evaluated the progression of retinal neurodegeneration by loss of thickness of mGCIPL measured using Cirrus HD-OCT. 17 Pinilla et al examined changes in retinal layer thickness by OCT in patients with type 1 DM who had no DR after 8 years of follow-up and found a significant difference in the thinning of the inner retinal layers compared with healthy controls. 31 Simó et al carried out a 2-year RCT to assess the efficacy of neuroprotective drug eye drops on retinal neurofunction in type 2 diabetic patients. 30 To test whether en face slab OCT imaging can assess temporal changes in the innermost retinal layer in diabetic eyes, we analyzed en face slab OCT image data from patients with DM who had been followed up with Cirrus HD-OCT for over 3 years.…”
Section: Discussionmentioning
confidence: 99%